2016 IEEE Photonics Society Summer Topical Meeting Series (SUM) 2016
DOI: 10.1109/phosst.2016.7548750
|View full text |Cite
|
Sign up to set email alerts
|

Optically integrated InP-Si3N4 hybrid laser

Abstract: We describe the first demonstration and characterization of an optically integrated InP-Si 3 N 4 hybrid laser. The laser is formed by integration of an InP-based reflective semiconductor optical amplifier with a Si 3 N 4 based feedback waveguide circuit. The circuit comprises a frequency selective and tunable Vernier mirror composed of two microring resonators with slightly different radii. A wide tuning range of more than 43 nm is achieved via the thermo-optic effect. The typical side mode suppression ratio i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The latter is achieved with extremely thick waveguide cores, fabricated with a novel approach of stepwise filling of pre-etched grooves [13]. This platform has also reached a considerable degree of maturity, allowing two-dimensional tapering [14] for low-loss fiber coupling or realizing hybrid lasers [15,16]. The platform supports also a wide range of optical functionalities [11,17] by offering various different core cross sections for waveguide dispersion engineering, and offers a highly reproducible material dispersion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The latter is achieved with extremely thick waveguide cores, fabricated with a novel approach of stepwise filling of pre-etched grooves [13]. This platform has also reached a considerable degree of maturity, allowing two-dimensional tapering [14] for low-loss fiber coupling or realizing hybrid lasers [15,16]. The platform supports also a wide range of optical functionalities [11,17] by offering various different core cross sections for waveguide dispersion engineering, and offers a highly reproducible material dispersion [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…One example of such hybrid integration is an integrated photonic beamformer using a modulator array in InP and a true-time-delay beamforming network in TriPleX [97] as shown in Figure 20. Also shown in Figure 20, Fan et al [32] recently demonstrated a narrow-linewidth laser which is based on a micro-assembly of a gain medium in InP and an external highly selective, low-loss filter in TriPleX. In this work, a key packaging challenge of chipto-chip coupling loss is addressed, which is critical for the performance of the laser.…”
Section: Device and System Development 71 Photonic Integrated Circuimentioning
confidence: 95%
“…More importantly, this system configuration is in favor of full system integration in one unit via the TriPleX-InP hybrid integration. While this particular reconfigurable RF filter has not been demonstrated in such a hybrid integration on the full scale, other parallel works have successfully demonstrated a unit based on the integration of a similar silicon nitride processor chip and an InP chip that provides active components [32]. These works will be discussed further in Section 5.…”
Section: Reconfigurable Filtersmentioning
confidence: 99%
See 2 more Smart Citations